STUDY OF THE MAGNETIC PROPERTIES OF POROUS POLYSTYRENE NANOPARTICLES LOADED WITH MAGNETITE - Puca, M. (2012)
In this work the synthesis of magnetite nanoparticles by coprecipitación in inverse microemulsion, which were introduced inside the pores of the polystyrene nanoparticles is reported. The nanoparticles of porous polystyrene were synthesized by heterogeneous polymerization in semicontinuo, which were employed like cover polymeric due to their biocompatibility and biostability. Through the analysis by X-ray diffraction was verified the structure of the magnetite, and estimated its average diameter of 9 nm. The polystyrene nanoparticles loaded with magnetite were prepared in different compositions magnetite/polymer and were determined by the test of magnetization that the magnetic moment (emu/g) is increased when the content of magnetite in the porous of polystyrene nanoparticles is increased.